Comportamento ingestivo, parâmentros hematológicos e bioquímicos de equinos submetidos à odontoplastia - PARENTE, Henrique Nunes (2024)
ABSTRACT: The aim of this study was to evaluate the effect of a dental procedure (odontoplasty) on the ingestive behavior and serum parameters of horses. Ten male, castrated Quarter Horses, aged approximately 80±7 months and weighing an average of 460±28 kg, housed at the André Lopes Training Center, were used. The animals were monitored on D0 (day 0, pre-dental treatment), D7 (seven days after dental treatment), D14 (fourteen days after dental treatment) and D21 (twenty-one days after dental treatment) to obtain ingestive behavior. Blood samples were collected on D0 and 14 and 28 days after odontoplasty (D14 and D28) to evaluate leukocyte, rod, segmented, lymphocyte, eosinophil, monocyte, erythrocyte packed cell volume (EVG), hemoglobin concentration (HB), mean packed cell volume (MVC), mean packed cell hemoglobin concentration (MHC), proteins, platelets, fibrinogen, oxaloacetic transaminase (AST/TGO), alanine aminotransferase (ALT/TGP) and creatine phosphokinase (CK). To perform the dental procedure, the animals fasted and were kept in a restraint cage, followed by a sedation protocol based on detomidine hydrochloride at a dose of 20 mcg/kg intravenously. The results of the variables were compared by the paired t-test, at 5% probability. There was no significant difference for the variables: time consuming concentrate (TCC), time consuming salt (TCS), time drinking water (TIA), period in idleness (PO), period lying down (PD) and time working (TT), with mean values of 63.8 (min); 3.2 (min); 66.5 (min); 734.6 (min); 98.1 (min) and 120.2 (min), respectively. There was no significant effect (p>0.05) for the variables: leukocytes, rods, eosinophils, erythrocytes, protein and fibrinogen, however, there was an effect (p<0.05) for the variables segmented, lymphocytes, VG, HB, VGM, CHGM and platelets. It is concluded that the odontoplasty technique, through correct interventions, prevents health problems and improves the hematological and biochemical profile of horses, as well as increases water intake and improves aspects related to the animals ingestive behavior.